Green Scale, Coccus viridis (Green) (Insecta: Homoptera: Coccidae) - Geo W. Dekle; Thomas R. Fasulo (EDIS)
The green scale, Coccus viridis (Green), an insect pest of citrus and other plants, is found out-ofdoors and in greenhouses in Florida. This pest was first found in Florida near Davie, Broward County in May 1942, by State Plant Board grove inspectors, and is now well established in south Florida. This insect is also referred to as the coffee green scale. This document is EENY-253 (originally published as DPI Entomology Circular 165), one of a series of the Department of Entomology, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Date printed: December 2001.